2022
DOI: 10.2147/mder.s360335
|View full text |Cite
|
Sign up to set email alerts
|

MRI Safety Practice Observations in MRI Facilities Within the Kingdom of Jordan, Compared to the 2020 Manual on MR Safety of the American College of Radiology

Abstract: Purpose The absence of ionizing radiation in MRI applications does not guarantee absolute safety. Implementing of safety guidelines can ensure high-quality practice in the clinical MRI with the minimum risk. For this purpose, this cross-section quantitative study conducted in Jordan Kingdom aimed to assess current MRI safety guidelines in comparison with those of 2020 Manual on MR Safety of the American College of Radiology (ACR). Patients and Methods A site observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…This finding was confirmed by the study of Siewert et al . (2019),[ 3 ] involving an academic radiology department, where 50% of the employees reported that owing to existing barriers, they spoke up about safety concerns less than 100% of the time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding was confirmed by the study of Siewert et al . (2019),[ 3 ] involving an academic radiology department, where 50% of the employees reported that owing to existing barriers, they spoke up about safety concerns less than 100% of the time.…”
Section: Discussionmentioning
confidence: 99%
“…In Saudi Arabia, as per law, health care providers should report any incidents or adverse events which are associated with medical devices occurring within their facilities (SFDA 2022). [ 4 ] Ayasrah (2022)[ 3 ] has concluded that there must be more practical approaches to improve MRI safety for both patients and health care workers. A recent assessment of magnetic resonance imaging (MRI) safety practices in Saudi Arabia has revealed that the majority of MRI units have demonstrated compliance with most of the safety recommendations; nonetheless, there are a few main items for which the guidelines may not be attained, like the absence of specialists and regular training programs to improve MRI safety practices for both patients and health care workers (Alghamdi 2023).…”
Section: Introductionmentioning
confidence: 99%
“…This is possibly due to the burden of financial commitment to organize periodic safety training, appoint an MRSO, or because Saudi Arabia’s Ministry of Health (MOH) does not mandate MRI safety training or an MRSO. 25 Ayasrah 26 found that only 4 of 38 facilities implemented MRI safety training courses in Jordan.…”
Section: Discussionmentioning
confidence: 99%